2019
DOI: 10.5897/ajbm2018.8678
|View full text |Cite
|
Sign up to set email alerts
|

Shareholders return and value of manufacturing firms listed on the Nigerian stock exchange

Abstract: The attainment of going concern concept of an entity relies heavily on its ability to maximize the wealth of its shareholders and value. The prospect of a firm to investors is a function of return, which signals to the market its good governance. The study examined the influence of shareholders' return on the value of manufacturing firms listed on Nigerian Stock Exchange using annual reports and accounts of 36 selected firms for a period of twenty years, between 2007 and 2016 (720 firm year observations). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
1
2
1
Order By: Relevance
“…The relationship between CSRTC and EVA {B4 = -16.449, P>0.05} is negative and not significant. This outcome is in line with the finding of the research of Oyeyemi, Enyi and Emmanuel (2019) where it was found that sales growth (an indicator of responsibility to customers) negatively and non-significantly influenced value of the firm.…”
Section: Test Of Hypothesis Foursupporting
confidence: 91%
See 1 more Smart Citation
“…The relationship between CSRTC and EVA {B4 = -16.449, P>0.05} is negative and not significant. This outcome is in line with the finding of the research of Oyeyemi, Enyi and Emmanuel (2019) where it was found that sales growth (an indicator of responsibility to customers) negatively and non-significantly influenced value of the firm.…”
Section: Test Of Hypothesis Foursupporting
confidence: 91%
“…Firm value is determined by the buying public (Exforsys, 2015). In the research of Oyeyemi, Enyi and Emmanuel (2019), it was found that growth in sales had non-significant negative effect on firm value while Neupane (2014) confirmed in UK Lloyds Bank that customer satisfaction and performance had a non-significant positive relationship (p=.139 or >.05; β=.343).…”
Section: Corporate Social Responsibility (Csr) To Customers and Econo...mentioning
confidence: 94%
“…Moreover, a number of studies claim that the dividend policy affects the value of the company (Mirna, 2020, Senata et al, 2016, Kim et al, 2020. The results of this investigation, however, are at odds with those of other studies (Risman, et al, 2020;Tamrin, et al, 2017;Anita and Yulianto, 2016;Oyeyemi and Emmanuel, 2019) that demonstrate that dividend policy has no bearing on firm value. According to research (Ivanov & Dolgui, 2020), debt policy positively and significantly affects a company's worth.…”
Section: Introductioncontrasting
confidence: 58%
“…The shareholders wealth maximization criterion proposed that managerial decisions in any organization should be centered on how to maximize the market value of the share or shareholders' wealth which is measured as market valuation (Khan & Hussanie, 2018). Market value is the stock exchange market share price as at the end of the financial year of all equity shares in issue (Ogundajo, Enyi, & Oyedokun, 2019).…”
Section: Review Of Conceptsmentioning
confidence: 99%